THE IMPACT OF “TRUMP’S POLICIES” ON ECONOMIC GROWTH IN SOUTHEAST ASIA: SYSTEMATIC LITERATURE REVIEW APPROACH - Muspida; Hermi Oppier; Dientje Rumerung; Hendri Dony Hahury (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the complex impact of President Donald Trump's "America First" protectionist economic policies on economic growth in the Southeast Asian region through the lens of Economic Realism theory. This study uses a qualitative approach with a descriptive analytical design. Data were collected through document studies in the form of official US policy data, ASEAN communiques, World Bank and IMF reports, and other academic literature, which were analyzed thematically based on the Economic Realism framework. The results reveal a dual impact. Trump's policies disrupted global supply chains and increased uncertainty. However, simultaneously, these policies opened up strategic opportunities in the form of trade diversion and investment relocation from China to Southeast Asia. The impact was not homogeneous, with Vietnam emerging as a major beneficiary, while countries with highly open economies experienced a slowdown. In aggregate, the region's economies demonstrated resilience driven by domestic demand and regional integration, leading to accelerated structural transformation. There are significant implications of Trump's policies regarding his role as a catalyst for accelerating economic diversification and building regional economic resilience. Therefore, to ensure sustainable growth, Southeast Asian countries need to continue strengthening regional cooperation and enhancing domestic competitiveness.